A one adsorbent QuEChERS method coupled with LC-MS/MS for simultaneous determination of 10 organophosphorus pesticide residues in tea. (15th August 2020) - Yu, Congcong; Hao, Dongyu; Chu, Qiao; Wang, Ting; Liu, Songnan; Lan, Tao; Wang, Fenghe; Pan, Canping
Highlights: A strategy to develop analysis method for trace analytes in a complicated matrix was given. Adsorption isotherm fitting was used to study the removal ability for tea matrix. π-π and electrostatic interaction may lead the adsorption. MWCNTs-NH2 can replace the combined effects of classical adsorbents. A method of MWCNTs-NH2 modified QuEChERS with good results was developed. Abstract: Tea polyphenols, chlorophyll and lutein generally cause strong matrix effects and challenge analysis of trace substances in tea. Seven frequently used adsorbents were chosen to test removal ability for tea polyphenols, chlorophyll and lutein based on the adsorption isotherm fitting. Results showed that MWCNTs-NH2 demonstrated the strongest removal ability, which may be ascribed to the π-π and electrostatic interaction. Then a method of MWCNTs-NH2 modified QuEChERS coupled with HPLC-MS/MS detection of 10 organophosphorus pesticide residues in tea was developed and validated. Unlike traditional QuEChERS, only one adsorbent (MWCNTs-NH2 ) was applied in this method to replace the combined effect of various adsorbents, which improved the easiness and generality of the method. The LOQs were 1.7–9.0 µg/kg. The average recovery rate ranged from 72% to 116% with RSDs less than 14%. This study provides a targeted strategy to develop analysis method for trace substances in a complicated matrix.